Desarrollo de una plataforma web, aplicada a una aula digital empleando la metodología OOHDM - Aguilar Bernabé, Roberto Jesús (2015)
The research in this paper has been to developed applied to even digital classroom, using the methodology OOHM, for which we had to investigate about software development methodologies and one in particular, which is Object-Oriented Hypermedia Design Method (OOHDM), which by way of proposal detailed in Chapter 2 of this research._x000D_ Investigate the development methodology OOHDM has given us a different view about the different development methodologies and usability understandable and formally, this is associated with this particular methodology is oriented Web platforms._x000D_ Therefore, it is necessary to establish the basic requirements involved in the problem. As a result of the research project concludes that through the developed of a web platform development methodology using OOHDM was achieved applying a digital classroom